A review of endothermal laser ablative treatment of incompetent saphenous veins - Schuler, L.; Hartmann, K. (Phlebologie, 2017)
Endovenous treatment of incompetent great and small saphenous veins has become firmly established as an alternative to cross-ectomy and stripping operations. Among other thermal and non-thermal procedures, endovenous laser ablation (EVLA) is one of the most frequently used methods. Development of the procedure has continued since its introduction in 1998: the low wavelengths used at first (810 nm) resulted in a high rate of complications (ecchymosis, pain), and over the years systems using longer wavelengths have been developed with increasingly fewer side effects. The effectiveness of the wavelength most frequently used today (1470 nm) has been reported in numerous studies. The most frequent side effects include endovenous heat-induced thrombosis (EHIT), nerve damage and ecchymosis; major complications like lung embolism are reported very rarely.
Keywords: Laser ablation; endothermal treatment; incompetent saphenous veins